Perancangan Sistem Informasi Monitoring Sales Karyawan Pada PT. Panen Lestari Indonesia (SOGO PVJ) - Syarif Hidayatulloh (Universitas Respati Indonesia, 2020)
Monitoring or supervision can be interpreted as an attempt to determine what is being done by assessing the results / accomplishments achieved and if there are deviations from the standards set, then immediately held repair business, so all results / accomplishments achieved in accordance with the plan In general monitoring is carried by leaders or superiors to subordinates. At PT. Panen Lestari Indonesia (SOGO PVJ) the supervision carried out by the leader or in this case the supervisor has not run optimally because there is no device used to help supervise the sales of each sales assistant and the sales assistant need to double check the sales that have occurred in the cashier to synchronize with the sales clerk have. This study aims to help supervisors to be able to supervise the sales of each salesperson on duty and to help the sales assistant to be able to check / synchronize sales that have occurred at the cashier more quickly and accurately. In developing this information system using the method prototype, the results of this research is the design of information system sales monitoring a-based employee web.